Estruturação do grupo Serra Grande região de Santana do Acaraú- CE e a reativação do lineamento Sobral Pedro II, integração com dados geofísicos - Carvalho, Marcelo José de (2003)
The study area is located in the NW portion of the Ceará state nearby the city of Santana do Acaraú. Geologically it lies along the Sobral-Pedro II lineament which limits the domains of Ceará Central and Noroeste do Ceará, both belonging to the Borborema Province.The object of study was a NE trending 30km long siliciclastic body (sandstone and conglomerate) bounded by transcurrent dextral faults. The sediments are correlated to the Ipú Formation (Serra Grande Group) from the Parnaiba basin, which age is thought to be Siluro-Devonian. Existing structural data shown that bedding has higher but variable dips (70-45) near the borders faults and much lower to subhorizontal inward the body. The brittle deformation was related to a reactivation, in lower crustal level, of the Sobral-Pedro II lineament (Destro (1987, 1999; Galvão, 2002).The study presented here was focused in applying geophysicals methods (gravimetry and seismic) to determine the geometry of the sandstone/conglomeratic body and together with the structural data, to propose a model to explain its deformation. The residual anomalies maps indicate the presence of two main graben-like structures. The sedimentary pile width was estimated from 2D gravimetric models to be about 500-600 meters. The 3D gravimetric model stressed the two maximum width regions where a good correlation is observed between the isopach geometry and the centripetal strike/dip pattern displayed by the sediments bedding. Two main directions (N-S and E-W) of block moving are interpreted from the distribution pattern of the maximum width regions of the sedimentary rock